Fatigue Failure Results for Multi-Axial versus Uniaxial Stress Screen Vibration Testing - Wayne E. Whiteman; Morris S. Berman (Shock and Vibration)
To date, the failure potential and prediction between simultaneous multi-axial versus sequentially applied uniaxial vibration stress screen testing has been the subject of great debate. In most applications, current vibration tests are done by sequentially applying uniaxial excitation to the test specimen along three orthogonal axes. The most common standards for testing military equipment are published in MIL-STD-810F and NAVMAT P-9492. Previous research had shown that uniaxial testing may be unrealistic and inadequate. This current research effort is a continuing effort to systematically investigate the differences between fatigue damage mechanisms and the effects of uniaxial versus tri-axial testing. This includes assessing the ability of the tri-axial method in predicting the formation of damage mechanisms, specifically looking at the effects of stress or fatigue failure. Multi-axial testing achieves the synergistic effect of exciting all modes simultaneously and induces a more realistic vibration stress loading condition. As such, it better approximates real-world operating conditions. This paper provides the latest results on the differences between multi-axial and uniaxial testing of a simple notched cantilever beam.